Maintaining quality of life in multiple sclerosis: fact, fiction, or limited reality? Mantendo a qualidade de vida na esclerose múltipla: fato, ficção ou realidade circunscrita? - Alina Gomide Vasconcelos; Vitor Geraldi Haase; Eduardo de Paula Lima; Marco Aurélio Lana-Peixoto (Arquivos de Neuro-Psiquiatria)
Health-related quality of life (HRQOL) is an important marker for health-related impacts on individuals with chronic diseases. This HRQOL study compares multiple sclerosis (MS) patients to a socio-demographically-matched healthy control group. HRQOL was assessed by means of a modular instrument (DEFU/DEFIS), which allows comparisons between diseased and healthy individuals. Main goal of the study was to obtain pertinent data to build a more reliable theoretical framework concerning HRQOL in MS. Another aim was to test the hypothesis of the so-called happiness paradox, according to which disabled individuals could maintain reasonable levels of HRQOL. Results show that MS individuals present lower levels of HRQOL in comparison to healthy controls, arguing against the happiness paradox hypothesis. Preservation of HRQOL levels against certain levels of disability may be restricted to a group of patients. A qualidade de vida relacionada à saúde (QVRS) é um indicador importante do impacto das doenças crônicas sobre a vida dos indivíduos. Esse estudo propõe uma comparação da qualidade de vida de uma amostra de portadores de esclerose múltipla (EM) e uma amostra pareada de indivíduos saudáveis, avaliada pelos questionários DEFU / DEFIS. O objetivo é contribuir para a construção de um referencial teórico a respeito do impacto das doenças crônicas e de seus tratamentos no bem-estar dos pacientes, assim como de investigar a hipótese do paradoxo da felicidade, segundo a qual os pacientes manteriam um bom nível de sensação de bem-estar apesar de suas incapacidades causadas pela doença. Os resultados mostraram que pacientes com EM apresentam graus mais baixos de QVRS do que indivíduos sadios, o que não corrobora a existência do paradoxo da felicidade. No entanto, é possível que a preservação da QVRS apesar das vicissitudes associadas à doença possa ser restrita a um grupo de pacientes.